Pengaruh Strategi Pembelajaran Contextual Teaching And Learning (Ctl) Dan Problem Based Learning (Pbl) Terhadap Hasil Belajar Matematika Ditinjau Dari Motivasi Belajar Siswa. - Chumairoh, Yesi, Drs. Ariyanto, M.Pd (2017)
The purpose of research this are: (1) The influence of learning strategies Contextual Teaching and Learning (CTL) and Problem Based Learning (PBL) against the result of the learning of mathematics. (2) The influence of students motivation to learn math results, (3) Testing the teraction of learning strategies Contextual Teaching and Learning (CTL) and Problem Based Learning (PBL) on the mathematics learning outcomes in terms of student motivation. antitative research with experimental design. The population in this study were all students of class X SMK Muhammadiyah Delanggu odd semester. Samples taken in this study were 38 students, consisting of 20 students as an experimental class and 18 students as the control class. The sampling technique used was simple random sampling. Data collection techniques through tests, questionnaires, and documentation. Prior to the analysis, first performed the balance test, test for normality and homogeneity test. Data were analyzed using two-way analysis of variance with a cell is not the same. The results of the data analysis with a significance level α = 5%, namely: (1) There is an effect of learning strategies on learning outcomes in mathematics. (2) There is an effect on learning outcomes motivation to learn mathematics. (3) There is no interaction learning strategies and students' motivation to learn math results. Keywords: Contextual Teaching and Learning (CTL), learning motivation, learning cooperative, Problem Based Learning (PBL).